The Impact of new information regime on the Indonesian Stock Exchanges: the weak form efficiency hypothesis / Husnizam Hosin, Nelmida and Vidiyanna Rizal Putri - Hosin, Husnizam; Nelmida; Rizal Putri, Vidiyanna (2018)
The efficiency of the emerging markets assumes greater importance as the trend of investments is accelerating in these markets as a result of regulatory reforms and removal of other barriers for international equity investments. This study provides empirical evidence on the impact of new information regime on the Indonesia Stock Exchanges: The Weak Form Efficiency Hypothesis. This study uses the data from the Composite Index before regulation changes from 1991 to 1995 and after regulation changes from 1996 to 2014. This paper employs the Simple Random Walk Test. The findings indicate that in general and exceptions the null hypothesis follow the random walk before and after regulation changes and are more prominent after the imposition of the new regime. The results suggest that it is difficult to reject the random walk hypotheses for most of the market return series after the regulatory reform. This result confirms that the market is weak-form efficient for monthly returns before and after regulation. The results also implied that the new information regime have impacted on the Indonesia Stock Exchange by making it more efficient.